Thromboelastography for the Prevention of Perioperative Venous Thromboembolism in Orthopedics. (April 2022) - Fan, Dejing; Ouyang, Ziyao; Ying, Yanping; Huang, Shuangxia; Tao, Pinyue; Pan, Xiao; Lu, Shuyu; Pan, Qini
We have reviewed a large number of relevant literature to determine the deficiencies of orthopedics in the diagnosis and prevention of venous thromboembolism（VTE）events during the perioperative period, and found that the TEG technology has been widely used after liver transplantation, which may make up for the deficiencies. This review expounds the detection principle and latest thromboelastography (TEG) development, and highlights the advantages of TEG over previous screening methods in diagnosing hypercoagulability. By analyzing the correlation and consistency between TEG and conventional coagulation test, reliable indexes for diagnosing hypercoagulability and important parameters for guiding perioperative anticoagulation treatment were summarized. Furthermore, our work contributes to further studies of TEG in orthopedics. Based on the research results, we believe that TEG may help orthopedists to identify and predict VTE events, use anticoagulants, eventually reduce the occurrence of VTE events.